2016
DOI: 10.1039/c6cp03944h
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric performance enhancement of Mg2Sn based solid solutions by band convergence and phonon scattering via Pb and Si/Ge substitution for Sn

Abstract: In this study, the thermoelectric properties of Mg2Sn0.98-xPbxSb0.02 were first studied, and then Mg2Sn0.93-xSixPb0.05Sb0.02 and Mg2Sn0.93-xGexPb0.05Sb0.02 were accordingly investigated. The results showed that the formation of Mg2Sn0.98-xPbxSb0.02 solid solutions effectively reduced the lattice thermal conductivity of Mg2Sn. The room temperature lattice thermal conductivity of Mg2Sn0.98Sb0.02 is ∼5.2 W m(-1) K(-1) but only ∼2.5 W m(-1) K(-1) for Mg2Sn0.73Pb0.25Sb0.02, a reduction of ∼52%. Further alloying Mg2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
42
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 45 publications
1
42
0
Order By: Relevance
“…In the present study, we focus on Mg 2 Sn with the same crystal structure as Mg 2 Si. Mg 2 Sn has been studied extensively as a potential TE material [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] . Xin et al 31 reported that an Sb-doped n-type polycrystalline Mg 2 Sn, Mg 2.15 Sn 0.98 Sb 0.02 exhibited a zT value of 0.53 at 650 K (κ and PF are 4.7 W/mK and 3.9 W/mK 2 , respectively).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we focus on Mg 2 Sn with the same crystal structure as Mg 2 Si. Mg 2 Sn has been studied extensively as a potential TE material [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] . Xin et al 31 reported that an Sb-doped n-type polycrystalline Mg 2 Sn, Mg 2.15 Sn 0.98 Sb 0.02 exhibited a zT value of 0.53 at 650 K (κ and PF are 4.7 W/mK and 3.9 W/mK 2 , respectively).…”
mentioning
confidence: 99%
“…Despite these sufficiently high PF values, the κ values are also high, limiting the zT values lower than ~0.5. Although the importance of controlling point defects in Mg 2 Sn is highlighted in some literature 29,31 , quantitative analysis of point defects has not been performed so far.…”
mentioning
confidence: 99%
“…The Lorenz number is used to calculate the lattice thermal conductivity lat + bi = − e = − . For the calculations we have assumed a scattering parameter of = −0.5, corresponding to carrier scattering by acoustic phonons beingdominant, an assumption that is considered to be well fulfilled for the material at temperatures above 300 K [8,13,48,51].…”
mentioning
confidence: 99%
“…Phonons can be effectively scattered by crystal defects and nanostructures, e.g., point defects [1][2][3][4][5][6][7][8][9][10][11][12], dislocations [13][14][15][16][17][18], grain boundaries [19][20][21][22][23], and nanoparticles/nanoprecipitates [24][25][26][27][28][29][30][31][32]. As one kind of defects, twins, which are often been observed in various material systems [33][34][35][36][37][38], its effect on phonon scattering is much less investigated comparing to other defects.…”
Section: Introductionmentioning
confidence: 99%